Transformation of T-lymphocyte subsets by Marek's disease herpesvirus. - Schat, K A (1991)
Marek's disease herpesvirus (MDV)-transformed lymphoblastoid tumor cell lines were characterized for the presence of the surface markers. Monoclonal antibodies were used for CD3 (T-cell receptor [TCR] complex), TCR1, TCR2, and TCR3, CD4, CD8, and Ia antigen by indirect fluorescence staining followed by microscopic examination or flow cytometry. The lymphoblastoid cell lines were obtained from tumors from chickens infected with MDV (n = 44) or from local lesions induced by inoculation of allogeneic, MDV-infected chick kidney cells (n = 56). Lymphocytes were harvested from these lesions between 4 and 16 days postinoculation and cultured in vitro to establish cell lines. All cell lines expressed Ia antigen and CD3 and/or TCR and thus are activated T cells. Most of the cell lines developed from tumors were CD4+ CD8-; only one cell line was negative for both markers. Sixteen percent of the cell lines were TCR3+, while the remainder were TCR2+. The cell lines developed from local lesions were much more heterogeneous: 45% were CD4- CD8+, 34% were CD4- CD8-, and only 21% were CD4+ CD8-. The number of TCR3+ cell lines was larger than expected for the CD4- CD8+ and CD4- CD8- cell lines, as judged from the presence of these cells in the blood. These results indicate that several subsets of T lymphocytes can be transformed by MDV, depending on the pathogenesis of infection. Activation of T cells as a consequence of the normal pathogenesis or by allogeneic stimulation seem to be a first important step in the process of transformation.